Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Cangkang Telur Ayam Ras Melalui Proses Sol Gel Dengan Variasi Waktu Reaksi Dan Waktu Aging - Audrya, Helsa; Azis, Yelmida; Akbar, Fajril (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite is a bioceramic widely used as bone and dental grafting, catalyst and adsorbent. Hydroxyapatite is a calcium phosphate compound that can be synthesized from natural sources having calcium content such as eggshells. Chicken eggshell is a waste has a 96.6% CaCO3 content. This study aims to synthesize hydroxyapatite through the formation of Precipitated Calcium Carbonate (PCC) from chicken eggshell. The research began with an eggshell calcination to form CaO which then made into PCC by carbonation method. PCC as a source of calcium was synthesized into hydroxyapatite using sol gel process varying reaction time (2; 3; 4 hours) and aging time (60; 65; 70 hours). The synthesized hydroxyapatite was analyzed by Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray (EDX) and Brunaur, Emmett and Teller (BET). The FTIR spectrums showed PO43- and OH- groups that indicate the forming of calcium phosphate compound. The XRD patterns showed the formation of hydroxyapatite compound from the 2Î¸ angle corresponding to the data of ICDD 01-073-6113. Hydroxyapatite synthesized at 4 hours reaction time and 70 hours aging time gave the best results with hexagonal crystal structure, crystal size of 26.91 nm, surface area of 43.272 m2/g and Ca/P ratio of 1.7.Keywords: aging, carbonation, PCC, sol-gel method.